(untitled) (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2018)
The normal-incidence reflectance spectrum of Bi40Ga2O63 single crystal in the energy range from 1 to 12 eV at room temperature has been measured. Single crystals have been grown using Top Seeded Solution Growth (TSSG) technique. Several peaks found in the reflectivity spectrum have been assigned to interband transitions at -Pline. Others structures are also discussed and interpreted in the terms of transitions between O2-(2p) states and conduction bands. The energy gap is indirect and lies between the top of the valence band at the G point and the bottom of the conduction band at the H point. أنجز قياس معامل طيف الانعكاس للبلورة الأحادية Bi40Ga2O63 في مجال الطاقة (1-12 eV) في غرفة ذات درجة حرارة. تمّت تنمية البلورات الأحادية باستخدام طريقة (TSSG). وقد لوحظ في طيف الانعكاس بنية غنية مطابقة للانتقالات الضوئية بين العصابات. وهي الحال التي فسرّت وجود قيم عدة في طيف الانعكاس بالانتقالات مابين العصابات على المستقيم G-P(L) . وفي ضوء ما تقدم فقد تمّت مناقشة بنى طيفية أخرى حيث فسرّت بدلالة الانتقالات مابين السويات O2- (2p) وعصابات الناقلية حيث تمّ تحديد عصابة الطاقة المحظورة كعصابة غير مباشرة مابين أعلى عصابة التكافؤ عند النقطة G وأسفل عصابة الناقلية عند النقطة H .